2008
DOI: 10.1016/j.fluid.2007.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Modelling liquid–liquid equilibria for island type ternary systems

Abstract: 5Closed miscibility gaps in ternary liquid mixtures, at constant temperature and pressure, are obtained if phase separations occur only in the ternary region, whilst all binary mixtures involved in the system are completely miscible. This type of behaviour, although not very frequent, has been observed for a certain number of systems. Nevertheless, we have found no information about the applicability of the common activity coefficient models, as NRTL and UNIQUAC, for these types of ternary systems. Moreover, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 11 publications
0
33
1
Order By: Relevance
“…We have found conditions for the NRTL binary parameters that allow the formation of island type ternary systems [62]. From a systematic study, it was concluded that the main requirement for the ternary LLE island region was the existence of a binary subsystem with a very low g M min value (dissimilar) compared to the other two binary subsystems.…”
Section: B Nrtl Binary Parameter Value Restrictions To Reproduce Islmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found conditions for the NRTL binary parameters that allow the formation of island type ternary systems [62]. From a systematic study, it was concluded that the main requirement for the ternary LLE island region was the existence of a binary subsystem with a very low g M min value (dissimilar) compared to the other two binary subsystems.…”
Section: B Nrtl Binary Parameter Value Restrictions To Reproduce Islmentioning
confidence: 99%
“…The representation of the sum of the conjugated binary interaction parameters (A ij + A ji ) versus the g M min value [62] showed that the negative values of such sum corresponded to the dissimilar binary and the positive sum corresponded to the other two binary subsystems. These conclusions led to the following restrictions for the dimensionless parameters, which are used in the equilibrium data regression of this type of system: Fig.…”
Section: B Nrtl Binary Parameter Value Restrictions To Reproduce Islmentioning
confidence: 99%
“…Explicit references to the use of parallel computing to fit equation of state (EOS) parameters could not be found in the literature. Although fitting EOS parameters is a seemingly routine problem, it is at least as complicated as fitting parameters of excess Gibbs energy models (Olaya et al, 2008, Staudt et al, 2013, and Soares and Gerber, 2013) and poses several challenges, which are often overlooked. Those relevant to this work are discussed in the next paragraphs.…”
Section: Introductionmentioning
confidence: 99%
“…In previous papers [22][23][24][25][26] robust calculation methods, based on the topological analysis of the Gibbs energy of mixing function (g M = ( mix G)/RT ), were developed. The topological analysis of g M is a valuable tool that allows deducing the geometrical conditions that the g M function has to fulfil, in order to reproduce certain equilibrium behaviour in the whole composition diagram, and clearly evidences any existing calculation inconsistency.…”
Section: Introductionmentioning
confidence: 99%
“…The previously developed methods [22][23][24][25][26] resulted in a robust computer program that has allowed the determination of the capabilities and limitations of the NRTL equation [27] for correlating equilibrium data between condensed phases in ternary systems. NRTL equation was selected as representative of thermodynamic local composition models, and is one of the most frequently used model.…”
Section: Introductionmentioning
confidence: 99%